Post-transfusion hemoglobin values and patient blood management. Issue 3 (4th May 2019) - Moerman, Jan; Vermeulen, Edith; Van Mullem, Mia; Badts, Anne-Mie; Lybeert, Peter; Compernolle, Veerle; Georgsen, Jørgen
Abstract: Objectives : The objective of this retrospective study was to evaluate the added value of communicating post-transfusion hemoglobin values to clinicians as a strategy to improve RBC utilization in a 500-bed hospital. Methods : The total number of RBC transfusions, the mean number of RBC units transfused per patient, the mean pre- and post-transfusion hemoglobin values, the ratio of patients transfused and the ratio of patients with a post-transfusion hemoglobin > 10.5 g/dL were calculated per service and per department for six months. The data were reported to each service and compared with the data of the department as peer group. The impact of this communication strategy was evaluated in the following six months. Results : In the six months pre-intervention, the mean post-transfusion hemoglobin value was 9.2 g/dL. Post-transfusion hemoglobin was > 10.5 g/dL in 13.4% of patients (112/835). Following communication of these data, RBC consumption decreased 21.0% ( p < 0.01) and 21% ( p < 0.01) fewer patients received transfusions despite an increase in mean post-transfusion hemoglobin value to 9.4 g/dL ( p < 0.01). Conclusion : Providing feedback on post-transfusion hemoglobin data and the global consumption of RBC units to prescribing physicians can be an additional, feasible and effective strategy to encourage self-assessment and to improve blood utilization.